Female genital tuberculosis - Matthys H. Botha; Frederick H. van der Merwe (South African Family Practice)
Mycobacterium tuberculosis has been identified as the aetiological agent of tuberculosis for many centuries. Genital tuberculosis is a chronic disease and often has low-grade symptomatology, with very few specific complaints. A study from South Africa found an incidence of 6% of culture-positive tuberculosis in an infertile population. The fallopian tubes are involved in most cases of genital tuberculosis and, together with endometrial involvement, cause infertility in patients. Many patients present with a symptom complex similar to that of ovarian carcinoma, i.e. abdominal distension, pelvic tumour and ascites, which may easily be confused with ovarian carcinoma. Biopsies should be obtained by either laparoscopy or laparotomy if examination of the ascitic fluid could not confirm the diagnosis. Genital tuberculosis is an elusive diagnosis and requires a high index of suspicion as a first step in the diagnostic process. Excellent cure rates are reported on all of the standard treatment regimens.